Environmental and biological lead absorption - Nagarajah, S. (My University, 1981)
In developing countries the safety gap between industrialization and' public health is s~ll alarmi~ly wide. Most of the industrial - opulation in Sri Lanka is working - . in small plante. Sra,allscale factories are vital in national economy, have substandard mana~ement8 with poor safety and he~lthy provision for the worker~ and 1'ar 1'rom the reach of community health;, service. The enviromnent in many 01'these work places leave much to be desired. Althoubh the plants of the existin~ industries were ins~alled at a time when safety standards were not known. There is little evidence that any of'these projects had in the plarming sta~e examined the operational history of similar project in other countries, where antipollution devices had satisfactory records or proved performances. In those countries where total elimination was technically impossible, devices of lower efficiency were reducing pollutont risks, while research was constantly in search 01'improvement. In develop~ng countries because of the lack of money, material and technological skill may make the process non-viable. In our country pollution hazards only become identiriable after the evidence of their danbers had mounted up. Due to rapid industrialization industries are croppin~ up with-out sufficient consideration, or even an understanding of their lon( term consequences to environment and their implication to human health and welfare. As a develop~ing country development of industrial resources is crucial for Sri Lanka. However cost of pollution control is prohibitively high, if we dont monitor the environment now, we may eventually ,reach a situation worse than the environmental problems faced by some of the highly de~elop~d countries. .-~-" - .- ._~ .., .....-1ead- had- wIde-industrial -uses". ..Ihdeec. '1t .uses has' been desci-IDea as" a: yard" 'stIck'o!'~ci vlllzatloL:'.'" Lead-contaIr.iuition', ~'aue- tc)the"ekisslon' rrori: rlidus.t'ry~ --, has existed for-a ~ery lo~'t1me: -In Srl-tai~a, ~et~lic lead is heated in o~en air and in ok-ellvessel, to produce lead oxides. This process performed without any protective devices like mask. There is no ventilation exhaust system. General condition of work are below normal and sanitary measures are poor and inadequate. Which in this case is the main cause of disturbance and intoxication is produced and scattered every where. Several contribut~one stressed the fact that present day ~aseline e~ineB had been I developed to run on hi~h octone leaded fuels and on immediate ban on the use of lead would results in loss of efficiency, hi~her fuel consumption and increased omission of other pollutants~ L So pollution due to lead will be unavoidable. Men will have to work with lead in industries, but they have to be protected a!ainst abnormal lead absorption and subsequent poisoni~. Therefore it is imperative to closely monitor the lead leavels in~ the workers to prevent resultir~ health hazards.